PENGETAHUAN DAN SIKAP PETANI DALAM PENGEMBANGAN USAHATANI PADI ORGANIK DI DESA SUMBER NGEPOH, KEC.LAWANG, KAB.MALANG, JAWA TIMUR. - Parsudi, Setyo (Berkala Ilmiah AGRIDEVINA, 2012)
Organic farming has good potential for the future mainly due to the negaitive effects of synthetic fertilizer (non-organic). Still, organic farming itself still has some of problems. Some of them are the limited number plants that can be grown and the limited production as well as the farmers who aren’t ready to apply and develop organic farming. Based on that background, this research aims to: 1) To find out how much far rice farmers know about organic farming, 2) To find out the farmers’ approach in developing organic rice farming, and 3) To find out the reasons of farmers who are willing as wwell as those who are unwilling to apply and develop organic rice farming. This research is a case study of Sumber Ngepoh village, Kecamatan Lawang, Kabupaten Malang, East Java in 2011. Sample gathering are done purposely in villages where organic rice are abundant and also because the region is a development area for organic rice-farming business in Kabupaten Malang. From the village, 20 respondents are taken which consists of 10 organic farmers and 10 non-organic farmers. The data are taken from the interviews with the respondents and then the result was analyzed and presented descriptively. The research found that the organic farmers’ knowledge regarding organic farming is generally good enough although incomplete. On the other hand, the non-organic farmers’ knowledge is still lacking especially regarding seed, soil, and post-harvest. All organic farmers are willing to develop their organic farms. On the other hand, most of the non-organic farmers are also willing but with some conditions. They want guidance from the expert. Those who still doubt the method and unwilling to apply it are in the minority. One reason why the farmers are willing to apply organic farming are due to its efficiency so that it can save them the money to buy fertilizers, pesticide, and labourers.